Nutrition in the Philippines: The Past for Its Template, Red for Its Color (Cecilia Florencio) - Cabilo, Zuraida Mae D. (Kasarinlan: Philippine Journal of Third World Studies, 2007)
Review of Nutrition in the Philippines: The Past for Its Template, Red for Its Color by Cecilia Florencio.
Keywords: Nutrition